Export Trend of Ready Made Garments (RMG) Sector of Bangladesh - Hossain, M. S.; Uddin, M. T. (Journal of Scientific Research, 2021)
Ready-Made Garments (RMG) sector has greater importance than any other sector in Bangladesh in terms of growth, employment, foreign exchange earnings and Gross Domestic Product (GDP). The objective of this study is to determine the export trend of the RMG sector in Bangladesh by using different trend models. To serve the objectives of the study, time-series data of RMG sectors has been used for the period 1985-2018. Among several trend models, the Semi-log Parabolic Trend model is found to be the best-fitted model for determining the trend of RMG exports. From the empirical results of the study, it is observed that RMG exports have a significant upward trend for the period 1985-2018 with a growth rate of 8.76 % in 2018. The forecasted RMG export will be nearly 31712.82 million USD in the financial year 2022-23. The findings of the study will help the government, NGO’s and policymakers to undertake necessary steps for the progress of this sector.